Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1109/tnsre.2019.2890968
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in Vibro-Tactile EEG Response and Its Implications in BCI Applications: A Comparison Between Older and Younger Populations

Abstract: The rapid increase in the number of older adults around the world is accelerating research in applications to support age-related conditions, such as brain-computer interface (BCI) applications for post-stroke neurorehabilitation. The signal processing algorithms for electroencephalogram (EEG) and other physiological signals that are currently used in BCI have been developed on data from much younger populations. It is unclear how age-related changes may affect the EEG signal and therefore the use of BCI by ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 42 publications
1
32
4
Order By: Relevance
“…We have not found any correlations of BCI performance with age, while it has been reported, that older subjects demonstrate inferior performance in tactile BCI 35 , and in ERP BCI in general. No correlation was found between subject age and the time, Interestingly, in the present study, the success in the tactile Braille reading task was correlated with success in completely different tasks of finger discrimination in BCI, despite what was claimed before 17 .…”
Section: Discussioncontrasting
confidence: 92%
“…We have not found any correlations of BCI performance with age, while it has been reported, that older subjects demonstrate inferior performance in tactile BCI 35 , and in ERP BCI in general. No correlation was found between subject age and the time, Interestingly, in the present study, the success in the tactile Braille reading task was correlated with success in completely different tasks of finger discrimination in BCI, despite what was claimed before 17 .…”
Section: Discussioncontrasting
confidence: 92%
“…In this study, we have not found any correlations of BCI performance with age, while it has been reported, that older subjects demonstrate inferior performance in tactile BCI [40], and ERP BCI in general. Also, no correlation was found between subject age and Braille reading speed.…”
Section: Discussioncontrasting
confidence: 81%
“…Previous studies have suggested that complications such as depression, cognitive impairment, aphasia, hemianopia, and unilateral neglect after stroke also affect the recovery of motor function (38). The presence of spontaneous speech is a favorable factor for the recovery of motor function (39,40). The present study showed that concomitant aphasia was an independent influencing factor of modest functional improvement of the distal UL in the patients.…”
Section: Discussionsupporting
confidence: 58%
“…The simplified FMA-UL score was categorized as severe (0-12), severe-moderate (13-30), moderate-mild (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47), and mild (48-60) (2). Because the initial FMA-UL scores of most patients were between severe-moderate to moderate-mild, a score of 30 was selected as the watershed in the following regression analysis.…”
Section: Functional Evaluationmentioning
confidence: 99%